2012
DOI: 10.1097/mpg.0b013e3182353773
|View full text |Cite
|
Sign up to set email alerts
|

MYO5B Mutations in Patients With Microvillus Inclusion Disease Presenting With Transient Renal Fanconi Syndrome

Abstract: : MYO5B mutations have divergent effects on the apical membrane system in kidney and intestinal epithelial cells. Epithelial defects presented in MVID are therefore likely triggered by intestine-specific factors, the identification of which may provide new targets and open avenues for the development of alternative therapeutic strategies to combat this devastating disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 32 publications
2
34
1
2
Order By: Relevance
“…El análisis genético también podría haber ayudado, el cual no está disponible en Chile aún. El Síndrome Fanconi, mencionado en la literatura internacional en dos casos parecidos 15 , fue transitorio y se atribuyó a una tubulopatía por deshidratación severa. La nefrocalcinosis es una complicación conocida relacionada con la malabsorción intestinal 16 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…El análisis genético también podría haber ayudado, el cual no está disponible en Chile aún. El Síndrome Fanconi, mencionado en la literatura internacional en dos casos parecidos 15 , fue transitorio y se atribuyó a una tubulopatía por deshidratación severa. La nefrocalcinosis es una complicación conocida relacionada con la malabsorción intestinal 16 .…”
Section: Discussionunclassified
“…Se describen múltiples complicaciones asociadas como el fallecimiento dentro del primer año de vida, el daño hepático crónico, nefrocalcinosis, retardo del desarrollo psico-motor, entre otras 15,16,17 . El trasplante intestinal es una opción terapéutica, solo o en combinación con hígado, aunque se pueden lograr sobrevidas aceptables con NPT a domicilio 18,19,20,21,22 .…”
Section: Introductionunclassified
“…This process is uncoupled from the establishment and maintenance of apical surface polarity as such. It is of interest to note that loss of Rab11a or myosin Vb function in hepatocytes did inhibit cell polarity (Wakabayashi et al, 2005), which raises intriguing questions about the role of the apical recycling endosomal system in relation to aspects of apical polarity in different types of epithelial cells (Golachowska et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from our group demonstrated disruption of apical polarity as a central feature of MVID long before Myo5b and STX3 were implicated in the disease (5). However, why loss of Myo5b results in severe intestinal disease and secretory diarrhea is not understood (17).…”
mentioning
confidence: 97%